2007
DOI: 10.1037/0893-164x.21.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the mediational influences of peer norms, environmental influences, and parent communications on heavy drinking in athletes and nonathletes.

Abstract: The present study used perspectives from the general literature on college alcohol consumption to examine mediational influences of peer, environmental, and parental variables on heavy drinking for student athlete and nonathlete samples. Eight hundred thirty-five freshmen who differed in organized sports involvement were compared on heavy drinking outcomes, peer norms, environmental influences, and parental communication. College athletes reported significantly more heavy drinking experiences than nonathletes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 57 publications
(103 reference statements)
4
79
0
2
Order By: Relevance
“…Recently, research has begun to focus on student athletes as a high-risk group Martens et al, 2006;Turrisi et al, 2006bTurrisi et al, , 2007. Student athlete alcohol misuse appears to be an exacerbation of patterns established before college (Hildebrand et al, 2001;Wechsler et al, 1997).…”
Section: Athletes As a High-risk Groupmentioning
confidence: 99%
“…Recently, research has begun to focus on student athletes as a high-risk group Martens et al, 2006;Turrisi et al, 2006bTurrisi et al, , 2007. Student athlete alcohol misuse appears to be an exacerbation of patterns established before college (Hildebrand et al, 2001;Wechsler et al, 1997).…”
Section: Athletes As a High-risk Groupmentioning
confidence: 99%
“…Self-concept theory seems to fit in well with the existing research. Several studies support the validity of using self-concept theory by demonstrating that different aspects of the self-schemas and self-identities that make up an individual's self-concept affect drinking behavior (Martens, Dams-O'Connor, et al, 2006;Meilman et al, 1999;NCAA, 2006;Nelson & Wechsler, 2001;Turrisi et al, 2007;Wilson et al, 2004;Yusko et al, 2008aYusko et al, , 2008b. Selfconcept theory and research support that studying college athletes separately is important because there are fundamental differences in the self-schemas and self-identity associated with college athletes and why they are consuming alcohol compared with why other college students are consuming alcohol (Martens, Dams-O'Connor, et al, 2006;Nelson & Wechsler, 2001;Turrisi et al, 2007;Wilson et al, 2004;Yusko et al, 2008b).…”
Section: Sport Participation and Drinking Behaviorsmentioning
confidence: 99%
“…In addition, the self-schemas and self-identity associated with a college athlete have many of the same qualities as those associated with a binge drinker. Turrisi et al (2007) investigated several social mediator variables of binge drinking in college athletes. Overall, they found that athletes get drunk significantly more often, engage in more episodes of heavy drinking, and drink more on their peak drinking occasion than nonathletes.…”
Section: Sport Participation and Drinking Behaviorsmentioning
confidence: 99%
“…Alcohol-related health problems, including morbidity and mortality, have been documented in youth populations, especially in university/college populations. Many factors have been found to mediate the association between alcohol use and related problems, including context of use (Courtenay, 2000;Fuchs & Le Hénaff, 2014), social determinants (Turrisi, Mastroleo, Mallett, Larimer, & Kilmer, 2007), significant others/sexual partners (Grossbard et al, 2007a), transition into adulthood (Allen-Collinson & Brown, 2012;Christie-Mizell & Peralta, 2009), socio-economic status (Bélanger, Ohl, Berchtold, Akre, & Suris, 2012), race/ethnicity (Neff, Prihoda, & Hoppe, 1991;Peralta & Steele, 2009), and gender identity norms (Iwamoto, Corbin, Lejuez, & MacPherson, 2014;Mahalik, Burns, & Syzdek, 2007;Moradi & Parent, 2013;Peralta, 2007). Also important is the nature of cultural activities associated with excessive alcohol use-for example, the formal and informal practices of sport as a highly gendered (and at times, gender-segregated) institution (Choquet & Com-Ruelle, 2009;Turrisi, Mallett, Mastroleo, & Larimer, 2006).…”
mentioning
confidence: 99%